New insights into carbon metabolism in Spathaspora passalidarum for second-generation ethanol production - Racca, Sofía; Leonardi, Rodrigo J.; Comelli, Raúl N. (Frontiers in Fungal Biology, 2025)
Bioethanol is a sustainable, low-impact energy source with the potential to reduce or even replace fossil fuel consumption. Second-generation (2G) bioethanol exploits lignocellulosic agro-industrial residues, contributing to circular economy strategies by valorizing these waste streams. However, conventional Saccharomyces cerevisiae strains are unable to efficiently metabolize the pentose sugars abundant in lignocellulose, prompting growing interest in non-conventional yeasts such as Spathaspora passalidarum. This species, recognized for its innate ability to assimilate pentoses, remains underexplored, particularly regarding its metabolic performance in mixed-sugar environments containing hexoses, pentoses, and disaccharides. Our results demonstrate that S. passalidarum’s xylose metabolism is strongly inhibited by pulses of hexoses such as glucose, galactose, and mannose, as well as by the disaccharide maltose. Notably, inhibition was also triggered by the non-metabolizable glucose analog 2-deoxyglucose (2DG), indicating that the regulatory signal originates during the early stages of glucose uptake into the cytosol rather than from downstream glycolytic pathways. In contrast, xylose metabolism was prioritized over fructose and sucrose. Furthermore, S. passalidarum was able to metabolize arabinose and glycerol, although these pathways favored biomass production through oxygen-dependent processes. Arabinose could be co-metabolized with xylose, but its assimilation was markedly suppressed in the presence of glucose. Collectively, these findings provide new insights into the metabolic regulation of S. passalidarum and highlight its potential role in the design of robust strategies for 2G bioethanol production.